Receptor-mediated transcytosis for brain delivery of therapeutics: receptor classes and criteria - Haqqani, Arsalan S.; Bélanger, Kasandra; Stanimirovic, Danica B. (Frontiers in Drug Delivery, 2024)
The delivery of therapeutics into the brain is highly limited by the blood-brain barrier (BBB). Although this is essential to protect the brain from potentially harmful material found in the blood, it poses a great challenge for the treatment of diseases affecting the central nervous system (CNS). Substances from the periphery that are required for the function of the brain must rely on active mechanisms of entry. One such physiological pathway is called receptor-mediated transcytosis (RMT). In this process, ligands bind to specific receptors expressed at the luminal membrane of endothelial cells composing the BBB leading to the internalization of the receptor-ligand complex into intracellular vesicles, their trafficking through various intracellular compartments and finally their fusion with the abluminal membrane to release the cargo into the brain. Targeting such RMT receptors for BBB crossing represents an emerging and clinically validated strategy to increase the brain permeability of biologicals. However, the choice of an appropriate receptor is critical to achieve the best selectivity and efficacy of the delivery method. Whereas the majority of work has been focused on transferrin (Tf) receptor (TfR), the search for novel receptors expressed in brain endothelial cells (BECs) that can deliver protein or viral vector cargos across the BBB has yielded several novel targets with diverse molecular/structural properties and biological functions, and mechanisms of transcytosis. In this review, we summarize well-studied RMT pathways, and explore mechanisms engaged in BBB transport by various RMT receptors. We then discuss key criteria that would be desired for an optimal RMT target, based on lessons-learned from studies on TfR receptor and accumulating experimental evidence on emerging RMT receptors and their ligands.